Navigating the Tech Frontier: Embracing Innovation in Modern Organizations - Faliza, Nur; Soraya Tanjung, Febrian; Suwarno (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2024)
This study investigates the impact of advanced technology adoption on competitive advantage at PT HM Sampoerna Tbk, focusing on the roles of change management and strategic alignment. Utilizing a quantitative research design with random sampling of 75 employees and analyzing data through Smart PLS, the research reveals that advanced technology adoption significantly enhances competitive advantage with a path coefficient of 0.60. Change management is identified as a critical mediator, with a significant indirect effect of 0.23, highlighting its importance in maximizing the benefits of technological advancements. Strategic alignment also influences competitive advantage, though its indirect effect through change management is marginally significant at 0.16. The findings underscore the necessity for organizations to effectively align technology adoption with strategic objectives and manage change processes to fully capitalize on technological innovations for sustained competitive success.